1986
DOI: 10.1056/nejm198610023151402
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Captopril and Enalapril in Patients with Severe Chronic Heart Failure

Abstract: To evaluate the concept that long duration of action is an advantageous property of angiotensin-converting enzyme inhibitors in the treatment of severe heart failure, we randomly assigned 42 patients to therapy with either a short-acting inhibitor (captopril, 150 mg daily) or a long-acting inhibitor (enalapril, 40 mg daily) for one to three months while concomitant therapy with digoxin and diuretics was kept constant. The treatment groups had similar hemodynamic and clinical characteristics at base-line evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(68 citation statements)
references
References 34 publications
1
65
2
Order By: Relevance
“…In the majority of clinical trials of ACE inhibitors in patients with heart failure, the reported incidence of symptomatic first-dose hypotension ranged from 2 to 33 % 8, 14, 21-24 . The randomized comparative trial by Packer et al confirmed the results of earlier non-comparative studies that demonstrated an increased frequency of early severe symptomatic hypotension, associated with renal failure and myocardial ischemia, in heart failure patients 24 . Subsequent studies, including 2 large, randomized controlled trials, also demonstrated this first-dose BP response.…”
Section: Clinical Consequencesmentioning
confidence: 64%
See 1 more Smart Citation
“…In the majority of clinical trials of ACE inhibitors in patients with heart failure, the reported incidence of symptomatic first-dose hypotension ranged from 2 to 33 % 8, 14, 21-24 . The randomized comparative trial by Packer et al confirmed the results of earlier non-comparative studies that demonstrated an increased frequency of early severe symptomatic hypotension, associated with renal failure and myocardial ischemia, in heart failure patients 24 . Subsequent studies, including 2 large, randomized controlled trials, also demonstrated this first-dose BP response.…”
Section: Clinical Consequencesmentioning
confidence: 64%
“…In this trial, the main reasons for lisinopril withdrawal were hypotension (9.7 % of patients) and renal impairment (2 %). Although it was not stated in either trial whether these effects were directly related to the first dose of the ACE inhibitor, there is evidence that the BP response to repeated administrations is directly related to the first-dose response 24,39 . Weber et al compared BP response in 205 patients with left ventricular dysfunction after AMI captopril and trandolapril.…”
Section: Myocardial Infarctionmentioning
confidence: 95%
“…21 Other studies have demonstrated that high doses of ACEI had a similar frequency of side effects to low doses in heart failure. 3,9,19 In contrast to those findings, it has been suggested that low doses of ACEI might be as effective as high doses, 8,16,17,20 but produce fewer side effects, especially the serious hypotensive effects 6,[21][22][23] that can compromise cerebral and renal function.…”
Section: Discussionmentioning
confidence: 97%
“…25 On the basis of these findings, we suggest that when ACEI are used in the treatment of patients with severe chronic heart failure, long-acting agents might reduce mortality more successfully than short-acting agents. 23 Notably, it remains to be evaluated why enalapril was superior to captopril, but factors such as ACEI lipophicidity and tissue converting enzyme inhibition, 26,27 rather than merely dose effect, may be important.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clear dissociation during chronic treatment between plasma angiotensin II and blood pressure reduction just discussed above demonstrates that this goal does not need to be reached. In fact, in some patients with congestive heart failure, it turned out that a marked and prolonged ACE inhibition may even be deleterious by increasing the incidence of renal failure (Packer et al, 1986). …”
Section: 'mentioning
confidence: 99%